Hubungan Pengetahuan Ibu Terhadap Pencegahan Stunting di Wilayah Kerja Puskesmas Gunung Kota Padang Panjang - Eka Desnita; Nopan Saputra; Yance Komela Sari (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Stunting is one of the health problems that Indonesia is still facing. Stunting is a growth and development disorder that causes a child to have a short or distant stature from the average child of his age. Stunting begins to occur when the fetus is still in the womb caused by the mother's food intake during pregnancy that is less nutritious. As a result, the nutrition obtained by the child in the womb is not sufficient. Stunting in children can be caused by various factors, ranging from genetic factors, lack of nutritional intake during the womb and after birth, repeated infections, to the low level of parental knowledge about the normal growth and development of children. This study aims to see the level of knowledge of mothers in preventing stunting in the work area of the city of Padang Panjang. This type of research is an analytic survey with a research design using a cross sectional study. The results of the study that the mother's level of knowledge was high with a percentage of 66.7%. while stunting prevention is not good with a percentage of 56.7%. The results of statistical tests obtained p value = 0.602, so it can be concluded that there is no significant relationship between the mother's level of knowledge on the prevention of stunting in the Gunung Padang Panjang Public Health Center in 2022. This study is expected to provide information about the mother's level of knowledge in preventing stunting